PEMBERDAYAAN SUMBER DAYA MANUSIA APARATUR PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SUMATERA SELATAN - Holipah Holipah; Asmawati Asmawati (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
In an organization, human resources have a crucial role to determine the achievement of organizational goals. Therefore, this study aims to determine the empowerment of human resources personnel at the Regional Employment Board of Central South Sumatra Province. The method used is descriptive-quantitative method. To obtain the data in forming a generalization, a number of samples and informants were used. The results shows that the empowerment of human resources personnel at the Regional Employment Board of Central South Sumatra Province is categorized ‘Good’, in which the average percentage score of all aspects are being reviewed as 77.42%. Nevertheless, there is still an aspect that needs to be noted that is the value of leadership, particularly leader’s justice in making decisions about the provision of learning tasks that should be more objective.